Potensi ekstrak tumbuhan Avicennia marina untuk mengendalikan jamur Colletotrichum sp. penyebab penyakit antraknosa pada cabai rawit (Capsicum frutescens) - Putri, Salsabila Sekar; Maryono, Tri; Rugayah, Rugayah; Pramono, Sudi (Jurnal Proteksi Agrikultura, 2024)
Cayenne pepper (Capsicum frutescens) is a horticultural commodity with high economic value and increasing demand. Anthracnose disease is a major limiting factor in cayenne pepper cultivation, with yield losses reaching up to 60%. Control of anthracnose is generally achieved through fungicide application. However, the extensive use of fungicides has led to the emergence of resistant strains and environmental pollution. Various plants have been reported to contain antifungal bioactive compounds. This study aims to determine the potential of mangrove extract to control Colletotrichum sp., the cause of anthracnose disease in cayenne pepper. The research was conducted at the Plant Disease Science Laboratory, Faculty of Agriculture, University of Lampung. The tested mangrove species were some part of Avicennia marina. In vitro testing was carried out using a poison food method and arranged in a completely randomized design with 5 replications. The treatments in the in vitro test included: no mangrove extract, extracts from the fruit, root, leaves, stem, and bark of A. marina. In vivo testing was conducted using a completely randomized design with 3 replications. The treatments consisted of: no mangrove extract, extracts from the root, leaves, stem, and bark of A. marina. The results indicate that extracts from various parts of A. marina inhibited the growth of Colletotrichum sp. colonies, except for extracts from A. marina root and leaf. However, all extracts from A. marina did not affect the sporulation of Colletotrichum sp., the cause of anthracnose in cayenne pepper. Furthermore, extracts from different parts of A. marina did not impede the occurrence or severity of anthracnose on cayenne peppers